Banco Canaima en la encrucijada. La nueva era Estratégica - Zavatti, Elvis (1993)
This case study develops the decision that must be made by the directors of a Venezuelan bank, Banco Canaima, in an unsophisticated market with a small number of competitors in the face of a reform of the financial system. It discusses what new strategy will be in the short, medium and long term and what direction the company should take: continue to grow or consolidate, as well as the concrete actions that would be taken in each case to implement the chosen strategy and to face the changes in the financial system and the increase of local and foreign competition. The purpose of this case study is to teach students the different obstacles that stand in the way of planning to change an organization’s strategy. Finally, marketing concepts may also be applicable to the activities of the banking sector.